Diagnostic delay and misdiagnosis in eosinophilic oesophagitis. Issue 12 (December 2021) - Lenti, Marco Vincenzo; Savarino, Edoardo; Mauro, Aurelio; Penagini, Roberto; Racca, Francesca; Ghisa, Matteo; Laserra, Giorgio; Merli, Stefania; Arsiè, Elena; Longoni, Valeria; de Bortoli, Nicola; Sostilio, Andrea; et al.
Abstract: Background: Eosinophilic oesophagitis (EoE) may lead to severe complications if not promptly recognised. Aims: To assess the diagnostic delay in patients with EoE and to explore its risk factors. Methods: EoE patients followed-up at eight clinics were included via retrospective chart review. Diagnostic delay was estimated as the time lapse occurring between the appearance of the first likely symptoms indicative of EoE and the final diagnosis. Patient-dependent and physician-dependent diagnostic delays were assessed. Multivariable regression models were computed. Results: 261 patients with EoE (mean age 34±14 years; M:F ratio=3:1) were included. The median overall diagnostic delay was 36 months (IQR 12-88), while patient- and physician-dependent diagnostic delays were 18 months (IQR 5-49) and 6 months (IQR 1-24). Patient-dependent delay was greater compared to physician-dependent delay (95% CI 5.1-19.3, p<0.001). A previous misdiagnosis was formulated in 109 cases (41.8%; gastro-oesophageal reflux disease in 67 patients, 25.7%). The variables significantly associated with greater overall diagnostic delay were being a non-smoker, >1 episode of food impaction, previous endoscopy with no biopsies, regurgitation, and ≥2 assessing physicians. Being single was significantly associated with lower overall and patient-dependent diagnostic delay. Conclusion: EoE is burdened by substantial diagnostic delay, depending on both patient-related and physician-related factors.